History vs. apologetics : the Holocaust, the Third Reich, and the Catholic Church - Cymet, David 1931- (Lexington Books, 2010)
Hitler's background -- Hitler in power, 1933 -- German rearmament -- Hitler's Grossdeutschland -- Catholic Europe 'defends' itself from the Jews -- World War II -- The Einsatzgruppen -- The death camps -- The final solution in Europe -- The Vatican response to the final solution -- Pius XII in the post war period (1945-1958)